2021
DOI: 10.3390/foods10081818
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Phytochemicals and the α-Glucosidase and α-Amylase Enzyme Inhibitory Effects of Nigella sativa Seed Extracts

Abstract: Nigella sativa L. (Ranunculaceae), commonly referred to as black seeds or black cumin, is used in popular medicine (herbal) all over the world for the treatment and prevention of several diseases, including diabetes. This study aims to investigate the inhibitory effect of N. sativa extracts and fractions against the activities of intestinal α-glucosidase and pancreatic α-amylase in vitro, and to explain the inhibitory effect of these fractions against these enzymes by identifying their active compounds respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
(82 reference statements)
1
32
0
Order By: Relevance
“…In this study, correlation analysis showed a significant positive correlation with naringenin and α-glucosidase inhibition (Pearson coefficient correlation (PCC) = 0.884, p = 0.017), as well as gallic acid and α-amylase inhibition (PCC = 0.833, p = 0.014). In our previous work, we have already demonstrated an interaction between gallic acid and α-amylase [ 16 ]. Here, we confirmed that naringenin has a higher affinity (ΔG = −7.2 kcal/mol) for interacting with α-glucosidase in its active site ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, correlation analysis showed a significant positive correlation with naringenin and α-glucosidase inhibition (Pearson coefficient correlation (PCC) = 0.884, p = 0.017), as well as gallic acid and α-amylase inhibition (PCC = 0.833, p = 0.014). In our previous work, we have already demonstrated an interaction between gallic acid and α-amylase [ 16 ]. Here, we confirmed that naringenin has a higher affinity (ΔG = −7.2 kcal/mol) for interacting with α-glucosidase in its active site ( Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Discovery Studio 2020 (Dassault Systemes, Vélizy-Villacoublay, France) was used to determine the type of interaction and visualize it in 2D, while UCSF Chimera 1.14 (San Francisco, CA, USA) was used to represent molecules and interaction residues in 3D. The docking protocol employed was described by [ 16 ]. The ligand’s 3D structure was obtained from PubChem (available online: (accessed on 25 August 2021)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have explored the biological properties of NS [ 6 – 8 ]. The plant has antibacterial effects against both Gram-positive and Gram-negative bacteria [ 9 ].…”
Section: Introductionmentioning
confidence: 99%